2019
DOI: 10.1152/ajprenal.00096.2019
|View full text |Cite
|
Sign up to set email alerts
|

Salt-sensitive increase in macrophages in the kidneys of Dahl SS rats

Abstract: Studies of Dahl salt-sensitive (SS) rats have shown that renal CD3+ T cells and ED-1+ macrophages are involved in the development of salt-sensitive hypertension and renal damage. The present study demonstrated that the increase in renal immune cells, which accompanies renal hypertrophy and albuminuria in high-salt diet-fed Dahl SS rats, is absent in Sprague-Dawley and SSBN13 rats that are protected from the SS disease phenotype. Flow cytometric analysis demonstrated that >70% of the immune cells in the SS k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 74 publications
3
26
0
Order By: Relevance
“…While SHR rats share important mechanistic features with Angiotensin II infusion model, it is, arguably, more representative of human disease (Doggrell and Brown, 1998). Another animal model used in the current investigation, Dahl salt-sensitive hypertension, capitalizes on different mechanisms of blood pressure regulation (Rapp, 1982) and commonly used to study salt-induced hypertension (Palygin et al, 2017;Fehrenbach et al, 2019;Lerman et al, 2019). Our current data obtained using a structurally unrelated compound further supports the critical involvement of PDE1 into the regulation of blood pressure via demonstration of therapeutic benefits in two independent rodent models of hypertension.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While SHR rats share important mechanistic features with Angiotensin II infusion model, it is, arguably, more representative of human disease (Doggrell and Brown, 1998). Another animal model used in the current investigation, Dahl salt-sensitive hypertension, capitalizes on different mechanisms of blood pressure regulation (Rapp, 1982) and commonly used to study salt-induced hypertension (Palygin et al, 2017;Fehrenbach et al, 2019;Lerman et al, 2019). Our current data obtained using a structurally unrelated compound further supports the critical involvement of PDE1 into the regulation of blood pressure via demonstration of therapeutic benefits in two independent rodent models of hypertension.…”
Section: Discussionsupporting
confidence: 61%
“…While SHR rats share important mechanistic features with Angiotensin II infusion model, it is, arguably, more representative of human disease (Doggrell and Brown, 1998). Another animal model used in the current investigation, Dahl salt-sensitive hypertension, capitalizes on different mechanisms of blood pressure regulation (Rapp, 1982) and commonly used to study salt-induced hypertension (Palygin et al, 2017;Fehrenbach et al, 2019;Lerman et al, 2019). Several studies have shown expression of PDE1 in the vascular wall (e.g., aorta, femoral, and mesenteric artery) of different rat strains, e.g., Wistar (Khammy et al, 2017;Laursen et al, 2017), Sprague Dawley (Giachini et al, 2011), and SHR rats (McMahon et al, 1989;Pontes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely acknowledged that low-grade or persistent inflammation is a key player in the development and maintenance of hypertension. Exhaustive research demonstrates the infiltration of immune cells, like T cells, macrophages, and dendritic cells in the kidneys, perivascular fat, or heart during the development and progression of hypertension [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In particular, immune cell transfer studies performed by Guzik et al [ 15 ] demonstrated that the development of angiotensin II-induced and DOCA salt-induced hypertension was dependent on the presence of T cells.…”
Section: Inflammation and Hypertensionmentioning
confidence: 99%
“…Study characteristics. Details on study characteristics can be found in Table 1 (part I) [12][13][14][15]20,[24][25][26][27][28][29][30][31][32][33][34][35] and Supplemental Table 3 (part II). 13,14,[18][19][20][21]33,[36][37][38][39][40] Of the 18 macrophage depletion studies (part I), 9 studies involved rat models, 8 involved mouse models, and one study involved both.…”
Section: Study Selectionmentioning
confidence: 99%